Inactivation of Scrapie Prions by the Electrically Charged Disinfectant CAC-717 - Akikazu Sakudo; Yoshifumi Iwamaru; Koichi Furusaki; Makoto Haritani; Rumiko Onishi; Morikazu Imamura; Takashi Yokoyama; Yasuhiro Yoshikawa; Takashi Onodera (Pathogens, 2020)
Previous studies have revealed that the electrically charged disinfectant CAC-717 has strong virucidal and bactericidal effects but is safe for humans and animals. In this study, CAC-717 was further evaluated for its potential effects as a disinfectant against scrapie prions. Western blotting showed that CAC-717 reduced the amount of the abnormal isoform of prion protein (PrPSc) in prion-infected cell (ScN2a) lysates. Furthermore, the reduction of prion transmissibility was confirmed by a mouse bioassay, in which mice injected with scrapie prions pre-treated with CAC-717 survived longer than those injected with untreated scrapie prions. Lastly, to evaluate the seeding activity of ScN2a cell lysates treated with CAC-717, quantitative protein misfolding cyclic amplification (PMCA) was performed directly on ScN2a cell lysates treated with CAC-717, which showed that the median dose of PMCA (PMCA50) dropped from log9.95 to log5.20 after CAC-717 treatment, indicating more than a 4 log reduction. This suggests that the seeding activity of PrPSc is decreased by CAC-717. Collectively, these results suggest that CAC-717 has anti-prion activity, reducing both PrPSc conversion activity and prion transmissibility; thus, CAC-717 will be useful as a novel disinfectant in prion diseases.